Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Giving Question dan Getting Answer Pada Konsep Sistem Gerak Terhadap Hasil Belajar Siswa SMAN 4 Bantimurung - Andi Asmawati, Azis; Rezeki, Amaliah (bionature, 2011)
This research aims to know biology-learning outcomes of the eleventh grade students SMAN 4 Bantimurung by implementing cooperative learning model type GQGA in Skeletal System Concept. This kind of research was queasy experimental with randomized control group only design. Subject of this research were all of XI IPA students of SMAN 4 Bantimurung in academic year 2011/2012, which consist of four classes. Research samples who respectively consist of 27 students, XI IPA that learned with cooperative learning model GQGA. The data analyzed in descriptive and inferential ways. The research result shows that scores of students who taught by implementing cooperative type GQGA are categorized good with the average score 75,04. The result of inferential statistic analyzed with t-test with sig (0.01) < α (0.05) so that H0 rejected and H1 received. From these results, it can be concluded that there is a differentiate students’ biology learning outcomes who are taught by implementing cooperative learning model Giving Question and Getting Answer type in the concept of Skeletal System at eleventh students SMAN 4 Bantimurung. The high scores of students’ the studying result which taught by implementing cooperative learning model type GQGA were caused by a lot of ideas or thought that can be shown by the students. Students were able to create problems with design questions and answer the questions.